Brain Derived Neurotrophic Factor and cognitive markers in subjects with Alzheimer’s disease - Naybí Prendes Rivero; Levis Verde Corvo; Belkis López González; Iris Dany Carmenate Rodríguez; Nibaldo B Mesa Hernández; María A Robinson Agramonte (Revista Habanera de Ciencias Médicas)
Introduction: The brain derived neurotrophic factor is a neurotrophin modulator of cognitive processes. Current studies in Alzheimer’s disease patients show alterations in biomarkers at outlying levels. Objective: To analyze the association between the serum brain-derived neurotrophic factor levels and the cognitive markers in Alzheimer’s disease subjects. Material and Methods: A correlational transversal study was conducted in subjects aged 64 years, distributed into three groups: group 1ː16 controls, group 2ː27 with mild cognitive impairment, and group 3ː21 with Alzheimer’s disease. A neuropsychological test battery, and the immunoenzymatic method (ELISA), Promega Emax Kit were applied to determine the serum brain-derived neurotrophic factor levels. The statistical analysis of data was performed using the one-way ANOVA test, the post-hoc Dunnett´s test and the Pearson’s correlation coefficient (p<0.05). Results: The serum brain-derived neurotrophic factor levels were lower in the groups with Alzheimer’s disease and mild cognitive impairment. The factor levels were correlated with the episodic memory, the executive functions, and the global cognitive function in Alzheimer’s disease patients. In the mild cognitive impairment group, the serum brain-derived neurotrophic factor was only associated with the executive functionl. Conclusions: The serum brain-derived neurotrophic factor levels diminish in association with cognitive impairment in Alzheimer’s disease. Furthermore, this factor linked to the executive domain dysfunction is suggested as a potential biomarker of neuroplasticity in the preclinical detection of this pathology.